THE IMPACT OF THE APPLICATION OF THE ACCOUNTING CONCEPT OF FAIR VALUE ON THE QUALITY OF FINANCIAL STATEMENTS OF BUSINESS ENTITIES IN BOSNIA AND HERZEGOVINA (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2019)
The primary objective of financial reporting in a modern market economy, which is based on the capital market, is to inform the investor about the financial position of a business entity. The unavoidable theme in modern accounting research is the valuation of balance sheet positions, regardless of the type and size of the business entity whose reports are the subject of this paper. The purpose of the research is to investigate whether there is a connection between the frequency of applying the accounting concept of fair value in valuing property positions and the quality of financial statements for businesses in Bosnia and Herzegovina. The target population comprises 34,515 small, medium and large enterprises registered as joint stock companies and limited liability companies in Bosnia and Herzegovina, and the questionnaire will be used as the empirical research instrument. The questionnaire is structured in parts to obtain knowledge about which technique or approach business entities use when using the fair value for the valuation of balance sheet items, and consequently how it affects the relevance, comprehensibility, comparability and credibility of the information presented in the financial statements.